Edukasi tentang Golongan Darah ABO dan Pemeriksaan Golongan Darah ABO pada Peserta Senam Jantung Sehat di Halaman Dinkes Provinsi Jayapura - Indra Taufik Sahli; Asrianto; Risda Hartati; Fajar Bakti Kurniawan; Afika Herma Wardani; Rina Purwati; Asrori (Jurnal Pengabdian Masyarakat Cendikia Jenius, 2025)
Blood type is essential information in health, particularly in blood transfusion procedures and medical emergency management. However, public awareness regarding the importance of knowing one's blood type remains low. This community service activity aimed to provide education and conduct blood typing using the ABO system for participants of the healthy heart exercise held at the Papua Provincial Health Office on November 9, 2024. The activity consisted of two main stages: health education on blood types and direct blood typing using the slide method. A total of 12 participants underwent the examination, with the following distribution of blood types: type A (50%), type O (25%), and type B (16.7%). These results reflect the tendency of blood type distribution, which is also influenced by genetic, ethnic, and geographical factors. It is concluded that blood type A is the most dominant among the participants of the healthy heart exercise (50%), followed by blood type O (25%) and blood type B (16.7%).